2017
DOI: 10.3892/ijmm.2017.3143
|View full text |Cite
|
Sign up to set email alerts
|

MAPK/p38 regulation of cytoskeleton rearrangement accelerates induction of macrophage activation by TLR4, but not TLR3

Abstract: Toll-like receptor 3 (TLR3) and TLR4 utilize adaptor proteins to activate mitogen-activated protein kinase (MAPK), resulting in the acute but transient inflammatory response aimed at the clearance of pathogens. In the present study, it was demonstrated that macrophage activation by lipopolysaccharide (LPS) or poly(I:C), leading to changes in cell morphology, differed significantly between the mouse macrophage cell line RAW264.7 and mouse primary peritoneal macrophages. Moreover, the expression of α- and β-tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Male C57BL/6J mice, 6–8 weeks old, were obtained from the Animal Research Committee of the Institute of Biology and Cell Biology (Shanghai, China) and housed in a specific environment as previously described . All animal experiments were undertaken in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals , with the approval of the Scientific Investigation Board of the Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…Male C57BL/6J mice, 6–8 weeks old, were obtained from the Animal Research Committee of the Institute of Biology and Cell Biology (Shanghai, China) and housed in a specific environment as previously described . All animal experiments were undertaken in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals , with the approval of the Scientific Investigation Board of the Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…The Kupffer cells of the liver are the first to be attacked by the damage produced, and express TLR4 to which lipopolysaccharides (LPS) bind. This produces the activation of NF-kB, mitogen-activated protein kinase (MAPK)[ 21 ] extracellular signal-regulated kinase-1 (ERK1), p38, c-jun N-terminal kinase (JNK) and interferon regulatory factor 3(IRF3)[ 22 ], which finally triggers the production of proinflammatory cytokines and enhances IFN-β and STAT1 expression[ 23 ]. The proinflammatory stimulus facilitates hepatocyte damage, contributing to the secretion of profibrogenic cytokines such as transforming growth factor beta (TGF-β) and the platelet-derived growth factor (PDGF), promoting the activation of HSCs.…”
Section: Activation Of the Innate Immune Response During Nafldmentioning
confidence: 99%
“…Previous studies demonstrated that LPS stimulation could activate MAPK signalling and lead to production of cytokines, including IL-6 and TNF-α in macrophages. 19 To explore the role of MAPK in macrophage activation induced by HBeAg, we performed Western blot experiment to detect the expression of non-phosphorylation and phosphorylation of MAPK in RAW264.7 cells treated with HBeAg. As can be seen in Figure 3A, the phosphorylated levels of key proteins in MAPK signal pathway, including ERK, JNK and p38, were all elevated after treatment with HBeAg and reached their peak at 30 minutes, and then began to decrease gradually at 60 minutes.…”
Section: Hbeag May Activate the Mapk Pathway Which Is Involved In Tmentioning
confidence: 99%